The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.1177/1750481315623902
|View full text |Cite
|
Sign up to set email alerts
|

Not so ‘innocent’ after all? Exploring corporate identity construction online

Abstract: While a lot of attention has been paid to online branding and the construction and communication of a company’s identity via its website, there is only very little research that looks at the processes involved in these activities from a discourse analytical perspective. This article aims to address this gap by conducting a case study of innocent, a UK producer of fruit juices. Combining corpus analytical tools with discourse analytical techniques and considering both text and multimodal features, we explore so… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(1 citation statement)
references
References 49 publications
0
1
0
Order By: Relevance
“…Previous work assuming such an angle has already shown that the way agency and action are encoded allows for inferring the ideologies that inform a text as well as for recognizing the possible intentions of the communicators. In terms of inferring underlying ideologies, studies have shown that the linguistic manifestations of agency and action can serve the strategic goals of individual organizations (The PAD Research Group, 2016;Pollach, 2005) but, perhaps more worryingly, even influence societal values and public policy. For example, in their analysis of AOL Time Warner's Internet policy document from the early 2000s, Amernic and Craig (2006) showed how the document refers to human stakeholders outside of the corporation.…”
Section: Agency and Action In Languagementioning
confidence: 99%
“…Previous work assuming such an angle has already shown that the way agency and action are encoded allows for inferring the ideologies that inform a text as well as for recognizing the possible intentions of the communicators. In terms of inferring underlying ideologies, studies have shown that the linguistic manifestations of agency and action can serve the strategic goals of individual organizations (The PAD Research Group, 2016;Pollach, 2005) but, perhaps more worryingly, even influence societal values and public policy. For example, in their analysis of AOL Time Warner's Internet policy document from the early 2000s, Amernic and Craig (2006) showed how the document refers to human stakeholders outside of the corporation.…”
Section: Agency and Action In Languagementioning
confidence: 99%